The Influence of Location, Store Atmosphere, Price, and CRM on Consumer Purchase Decision at The Milk Bar Bandung - Annisa Lisdayanti (Jurnal Akuntansi, Manajemen dan Ekonomi, 2017)
The level of milk consumption in Indonesia is only 11.48 kg/capita per year, this is still very much lower compared to other countries in Asia. The amount of milk consumption of Indonesia is less than Malaysia, Indian, Singapore, Thailand, Vietnam, and Philippines. Bandung is an area rich in culinary. One of the culinary places in Bandung is The Milk Bar. To improve the consumer purchase decision, so the strategy of location, store atmosphere implementation, CRM implementation, and price implementation need to be considered well by the company. This research is descriptive and verificative, with sample of 115 consumers of The Milk Bar obtained by 3 times iteration calculations. The results showed that from the four independent variables studied, the results obtained that the location has a greater influence in improving purchase decision. And together obtained a value of 77.4% and the remaining 22.6% influenced by other variables not examined in this study.